Comment on "amplification of endpoint structure for new particle mass measurement at the LHC" - Barr, A; Gwenlan, C; Lester, C; Young, C (2011)
We present a comment on the kinematic variable m CT2 recently proposed in Won Sang Cho, Jihn E. Kim, and Ji-Hun Kim, Phys. Rev. D 81, 095010 (2010). The variable is designed to be applied to models such as R-parity conserving supersymmetry (SUSY) when there is pair production of new heavy particles each of which decays to a single massless visible and a massive invisible component. It was proposed by Cho, Kim, and Kim that a measurement of the peak of the m CT2 distribution could be used to precisely constrain the masses of the SUSY particles. We show that, for the an example characterized by direct squark decays, when standard model backgrounds are included in simulations, the sensitivity of the m CT2 variable to the SUSY particle masses is more seriously impacted for m CT2 than for other previously proposed variables. © 2011 American Physical Society.